ANALISIS NILAI TAMBAH PRODUK AGROINDUSTRI PERMEN SUSU DI KECAMATAN MOYO UTARA KABUPATEN SUMBAWA - Try Wasjud Waqtarib; Taslim Sjah; L Sukardi (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2020)
ABSTRACT The objectives of this study are (1) To analyze the added value of a Milk Candy agroindustry business in North Moyo District, Sumbawa Regency (2) To analyze how much profit the Milk Candy agroindustry business is in the North Moyo District Sumbawa Regency (3) To identify the obstacles faced by the agroindustry business Milk Candy in North Moyo District, Sumbawa Regency. The method used in this research is descriptive method which is a method that aims to solve problems that occur at the present time by collecting data, compiling data, analyzing data and then drawing conclusions. The unit of analysis in this research is the milk candy agro-industry in North Moyo District, Sumbawa Regency. This research was conducted in North Moyo District, Sumbawa Regency. North Moyo Subdistrict consists of 6 villages namely, Baru Tahan Village, Kukin Village, Penyaring Village, Pungkit Village, Sebewe Village and Songkar Village. Of the six villages, the Filter Village was designated as a research sample area (purposive sampling) based on the consideration that there was a milk candy agroindustry in the Filter Village, North Moyo District, Sumbawa Regency. Respondents in the study were conducted in a census meaning that all existing and still active agro-industry entrepreneurs in the Filter Village of North Moyo District were used as respondents. Analysis of the data used in this study includes: Value Added Analysis, Profit Analysis, and Obstacle Analysis using descriptive methods. The results of this study indicate that the average value added obtained by milk candy agroindustry respondents in North Moyo Subdistrict, Sumbawa Regency is Rp. 16,445 / liter with an added value ratio of 41.52%. The average profit on the milk candy agro-industry in North Moyo District, Sumbawa Regency is Rp 225,984 / Production process or Rp 5,875,508 / month. Obstacles faced by milk candy agro-industry entrepreneurs in North Moyo Subdistrict, Sumbawa Regency include: (1) continuity of raw material availability (2) limited marketing reach of milk candy production. For fresh cow dairy entrepreneurs who want to get the maximum profit, it is recommended that the availability of raw milk candy agro-industry raw materials is sufficiently available to meet the needs of milk candy entrepreneurs.